Programmable robot control system
By designing a programmable robot control system that includes a flexible humidity sensor array and a contactless control system, the problem of bacteria or virus transmission caused by contact control is solved, and a safe and flexible contactless control effect is achieved.
Patent Information
- Application Number
- CN202411702198.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-26
AI Technical Summary
In the prior art, controlling programming robots through contact means can easily cause the spread of bacteria or viruses.
A programmable robot control system including a flexible humidity sensor array, energy storage module, resistance acquisition device, Bluetooth and robot control end is designed. By changing the resistance value of the humidity sensor by non-contact sliding fingers, non-contact control of the robot is realized.
Controlling robots through contactless means reduces the risk of bacteria or virus transmission and improves the flexibility and safety of robot control.
Smart Images

Figure CN119526398A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of robot control, and in particular to a programmable robot control system. Background Art
[0002] In the context of the Internet of Things era, most switches or interfaces used for human-machine interaction HMI require manual touch to respond, which inevitably causes equipment wear and aging, affecting its cleanliness. Especially in the case of the prevalence of infectious viruses or bacteria, human-machine interaction interfaces in public places such as elevator buttons and ATM machines require non-contact operation to isolate the spread of viruses or bacteria. The water content of human skin can account for 20% of the total water content of the human body, and the humidity on the surface of the skin will be significantly different from the ambient humidity, which makes it possible to control the machine non-contactly through the humidity sensor HS. Based on this technology, it is expected to control programmable robots in a non-contact manner.
[0003] Therefore, there is a need for a programmable robot control system that can reduce the spread of bacteria or viruses in a non-contact manner. Summary of the invention
[0004] The main purpose of the present invention is to provide a programmable robot control system to solve the problem in the prior art that controlling a programmed robot by contact easily causes the spread of bacteria or viruses.
[0005] To achieve the above-mentioned purpose, the present invention provides a programmable robot control system, comprising: a flexible humidity sensor array, an energy storage module, a resistance acquisition device, Bluetooth and a robot control terminal; the energy storage module powers the resistance acquisition device and Bluetooth, the flexible humidity sensor array is connected to the resistance acquisition device, the resistance acquisition device uploads the collected data to the robot control system via Bluetooth, and the robot control system processes the data and converts the data into corresponding control signals to control the movement of the programmable robot.
[0006] Furthermore, the resistance acquisition module has multiple channels, and the multiple channels simultaneously acquire the resistance values of multiple flexible humidity sensors on the flexible humidity sensor array.
[0007] Furthermore, the energy storage module includes: a DC power supply, or a triboelectric nanogenerator TENG, or an electromagnetic generator EMG, or other energy supply equipment.
[0008] Furthermore, the preparation method of the flexible humidity sensor comprises the following steps:
[0009] S1, preparation of Ag / PEDOT:PSS material.
[0010] S2, preparing an interdigitated electrode substrate.
[0011] S.3, use screen printing to print Ag / PEDOT:PSS material onto the interdigital electrodes to complete the preparation of the flexible humidity sensor.
[0012] Furthermore, step S1 specifically includes the following steps:
[0013] S1.1, prepare 3,4-ethylenedioxythiophene EDOT as a monomer, polystyrene sulfonate PSS as a dopant, and sodium persulfate Na2S2O8 as an oxidant.
[0014] S1.2, dissolve 2g PSS in 100ml water, and then add 1g Na2S2O8 oxidant to form a uniform solution.
[0015] S1.3, dissolve 0.5 mM silver nitrate AgNO3 in deionized water to prepare an AgNO3 solution, and add it to the solution obtained in step S2.
[0016] Furthermore, it is characterized in that step S1 also includes the following steps:
[0017] S1.4, prepare a reducing agent solution with 10 mM sodium borohydride NaBH4, and slowly add the NaBH4 solution and 5 g EDOT monomer into the solution under stirring conditions.
[0018] S1.5, magnetic stirring at 0°C for 24 hours, adding 10 mM citric acid C6H8O7 as a stabilizer during the reaction and stirring to finally obtain a PEDOT / PSS solution doped with Ag nanoparticles.
[0019] S1.6, after the reaction is completed, the mixture is washed with deionized water to remove residual oxidants and unreacted monomers, and then centrifuged and purified for 10 h in a centrifuge to obtain pure Ag / PEDOT:PSS material.
[0020] Furthermore, step S2 specifically includes the following steps:
[0021] S2.1, select a flat flexible PCB circuit board with polyimide as the substrate.
[0022] S2.2, a layer of Cu / Ni metal film is uniformly sputtered on the surface of the PCB circuit board to form an interdigitated meander-shaped electrode.
[0023] S2.3, a uniform, highly adherent and defect-free photoresist film is coated on the surface of the PCB circuit board by spin coating.
[0024] S2.4, using a photolithography machine to irradiate the PCB circuit board covered with the mask plate with ultraviolet light, so that the solubility of the photoresist in the illuminated area changes.
[0025] S2.5, immersing the PCB circuit board covered with the mask plate in a developer to remove the photoresist of the unexposed portion to form a three-dimensional mask pattern.
[0026] S2.6, using wet etching technology to remove the Cu / Ni film not protected by the photoresist in the mask pattern, thereby forming a forked-finger metal electrode on the surface of the PCB circuit board.
[0027] S2.7, removing the remaining photoresist through a stripping process, leaving only the Cu / Ni electrode pattern formed on the surface of the PCB circuit board, thereby forming an interdigitated electrode substrate.
[0028] Furthermore, step S3 specifically includes the following steps:
[0029] S3.1, fix the pre-processed screen printing plate on the interdigital electrode substrate, use a scraper to apply pressure on the interdigital electrode substrate, and move from one end of the screen printing plate to the other end, so that the Ag / PEDOT:PSS material passes through the pattern area of the screen and is evenly squeezed onto the interdigital electrode substrate to form a thin film with a specific pattern.
[0030] S3.2, annealing the obtained thin film and the interdigital electrode substrate at 230° C. for 30 minutes in a glove box filled with nitrogen to complete the preparation of the flexible humidity sensor.
[0031] Furthermore, the planar flexible PCB circuit board has a size of 1×1.2 cm and a bottom plate thickness of 1 mm.
[0032] Furthermore, the effective area of the Cu / Ni electrode of the interdigitated electrode substrate is 8×6 mm, the electrode line width and line gap are both 200 μm, and the thickness is 20 μm.
[0033] The present invention has the following beneficial effects:
[0034] The present invention introduces Ag nanoparticles into PEDOT, uses polystyrene sulfonic acid (PSS) as a dopant, forms Ag / PEDOT:PSS material, designs a humidity sensor with good conductivity and flexibility, and applies the humidity sensor to the control system of the editable robot. The morphology and molecular structure of Ag / PEDOT:PSS are clearly understood by characterization methods such as SEM, TEM, XRD and XPS. Then, a high-precision humidity sensor is manufactured on a circular electrode substrate by screen printing. Ag / PEDOT:PSS combines the high conductivity of silver nanoparticles with the excellent film-forming property, flexibility and humidity response characteristics of PEDOT:PSS, showing excellent sensing performance: humidity signal response (219%), response / recovery time (2.3s / 16.2s@83% humidity), repeatability and long-term stability (greater than 30 days), etc. The excellent working performance and simple use method make it widely used in wearable devices, education and training, smart medical and other fields. It provides technical possibilities for the intelligent transformation of the social welfare industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the specific implementation of the present invention or the technical solutions in the prior art, the following will briefly introduce the drawings required for the specific implementation or the prior art description. Obviously, the drawings described below are some implementations of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. In the drawings:
[0036] Figure 1 A structural diagram of a programmable robot control system of the present invention is shown.
[0037] Figure 2 Shown is a SEM image of the PEDOT:PSS material.
[0038] Figure 3 SEM images of Ag materials are shown.
[0039] Figure 4 Ag / PEDOT:PSS material is shown.
[0040] Figure 5 TEM images of PEDOT:PSS materials are shown.
[0041] Figure 6 TEM images of Ag materials are shown.
[0042] Figure 7 The Ag element distribution diagram in Ag / PEDOT:PSS material is shown.
[0043] Figure 8Shown is the distribution diagram of C element in Ag / PEDOT:PSS material.
[0044] Fig. 9 The figure shows the distribution of O element in Ag / PEDOT:PSS material.
[0045] Fig.10 The figure shows the distribution of S element in Ag / PEDOT:PSS material.
[0046] Fig.11 The xrd patterns of Ag, PEDOT:PSS and Ag / PEDOT:PSS materials are shown.
[0047] Fig.12 The total measured spectrum is shown.
[0048] Fig.13 The spectrum of Ag is shown.
[0049] Fig.14 The spectrum of O1s is shown.
[0050] Fig.15 The spectrum of c 1s is shown.
[0051] Fig.16 The spectrum of S2p is shown.
[0052] Fig.17 The resistance curves of sensors made of PEDOT:PSS material and Ag / PEDOT:PSS material under different humidity conditions are shown.
[0053] Fig.18 The response curves of the sensors made of Ag and Ag / PEDOT:PSS materials at different humidity levels are shown.
[0054] Fig.19 The fitting curves of the responses of the sensors of Ag and Ag / PEDOT:PSS materials at different humidity are shown.
[0055] Fig. 20 The uplink and downlink test curves of sensors made of Ag and Ag / PEDOT:PSS materials are shown.
[0056] Fig.21 The hysteresis characteristic diagram of the sensor made of Ag / PEDOT:PSS material when the relative humidity is 0-97%.
[0057] Fig. 22 Response / recovery time graphs at 83% humidity are shown for sensors of Ag and Ag / PEDOT:PSS materials.
[0058] Fig.23The graph shows the response curve of the sensor made of Ag / PEDOT:PSS material when it is continuously tested under 0-97% humidity.
[0059] Fig.24 The repeatability curve graph of the sensor of Ag / PEDOT:PSS material under the conditions of humidity 10% and 50% is shown.
[0060] Fig.25 The stability curve of the sensor made of Ag / PEDOT:PSS material under different humidity conditions is shown.
[0061] Fig.26 Shown are the response curves of the sensor based on Ag / PEDOT:PSS material for fast, normal and slow breathing.
[0062] Fig. 27 Graphs showing the response of the sensor based on Ag / PEDOT:PSS material to deep and shallow breathing. DETAILED DESCRIPTION
[0063] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0064] Embodiment 1
[0065] like Figure 1 As shown, a programmable robot control system includes: a flexible humidity sensor array, an energy storage module, a resistance acquisition device, Bluetooth and a robot control end; the energy storage module powers the resistance acquisition device and Bluetooth, the flexible humidity sensor array is connected to the resistance acquisition device, the resistance acquisition device uploads the collected data to the robot control system via Bluetooth, and the robot control system processes the data and converts the data into corresponding control signals to control the movement of the programmable robot. The non-contact sliding of the finger on the flexible humidity sensor array can change the resistance value of the flexible humidity sensor. After receiving these time-varying electrical signals, the programmable robot will make a series of actions, such as walking forward, walking backward and turning left. The resistance acquisition device collects the resistance value of each flexible humidity sensor and transmits it to the wireless receiving module on the robot via Bluetooth wireless. After receiving the resistance value of the flexible humidity sensor array, the robot control end processes the data and converts it into corresponding control signals to control the movement of the robot. In addition, the system is expected to control ATMs, elevators, robots, drones and robot vehicles in a non-contact manner.
[0066] Specifically, the resistance acquisition module has multiple channels, and the multiple channels simultaneously acquire the resistance values of multiple flexible humidity sensors on the flexible humidity sensor array. The resistance values are wirelessly transmitted to the robot control end via Bluetooth. The robot control end will process the received resistance data to obtain the humidity of each flexible humidity sensor and execute the corresponding response program according to the humidity results.
[0067] Specifically, the energy storage module includes: a DC power supply, or a triboelectric nanogenerator TENG, or an electromagnetic generator EMG, or other energy supply equipment.
[0068] Specifically, the preparation method of the flexible humidity sensor includes the following steps:
[0069] S1, preparing Ag / PEDOT:PSS material. PEDOT is poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate.
[0070] S2, preparing an interdigitated electrode substrate.
[0071] S.3, use screen printing to print Ag / PEDOT:PSS material onto the interdigital electrodes to complete the preparation of the flexible humidity sensor.
[0072] Specifically, step S1 includes the following steps:
[0073] S1.1, prepare 3,4-ethylenedioxythiophene EDOT as a monomer, polystyrene sulfonate PSS as a dopant, and sodium persulfate Na2S2O8 as an oxidant.
[0074] S1.2, dissolve 2g PSS in 100ml water, and then add 1g Na2S2O8 oxidant to form a uniform solution.
[0075] S1.3, dissolve 0.5 mM silver nitrate AgNO3 in deionized water to prepare an AgNO3 solution, and add it to the solution obtained in step S2.
[0076] Specifically, it is characterized in that step S1 also includes the following steps:
[0077] S1.4, prepare a reducing agent solution with 10 mM sodium borohydride NaBH4, and slowly add the NaBH4 solution and 5 g EDOT monomer into the solution under stirring conditions.
[0078] S1.5, magnetically stirred at 0°C for 24 hours. In order to prevent the aggregation of Ag nanoparticles, 10 mM citric acid C6H8O7 was added as a stabilizer and stirred during the reaction to finally obtain a PEDOT / PSS solution doped with Ag nanoparticles; EDOT was polymerized into PEDOT under the action of Na2S2O8 gallium oxide, and PSS played a doping role, enhancing the conductivity of PEDOT.
[0079] S1.6, after the reaction is completed, the mixture is washed with deionized water to remove residual oxidants and unreacted monomers, and then centrifuged and purified for 10 h in a centrifuge to obtain pure Ag / PEDOT:PSS material.
[0080] Specifically, step S2 includes the following steps:
[0081] S2.1, select a flat flexible PCB circuit board with polyimide as the substrate.
[0082] S2.2, a layer of Cu / Ni metal film is uniformly sputtered on the surface of the PCB circuit board to form an interdigitated meander-shaped electrode.
[0083] S2.3, a uniform, highly adherent and defect-free photoresist film is coated on the surface of the PCB circuit board by spin coating to facilitate subsequent pattern transfer.
[0084] S2.4, using a photolithography machine to irradiate the PCB circuit board covered with the mask plate with ultraviolet light, so that the solubility of the photoresist in the illuminated area changes.
[0085] S2.5, immersing the PCB circuit board covered with the mask plate in a developer to remove the photoresist of the unexposed portion to form a three-dimensional mask pattern.
[0086] S2.6, using wet etching technology to remove the Cu / Ni film not protected by the photoresist in the mask pattern, thereby forming a forked-finger metal electrode on the surface of the PCB circuit board.
[0087] S2.7, removing the remaining photoresist through a stripping process, leaving only the Cu / Ni electrode pattern formed on the surface of the PCB circuit board, thereby forming an interdigitated electrode substrate.
[0088] Specifically, step S3 includes the following steps:
[0089] S3.1, fix the pre-processed screen printing plate on the interdigital electrode substrate, use a scraper to apply pressure on the interdigital electrode substrate, and move from one end of the screen printing plate to the other end, so that the Ag / PEDOT:PSS material passes through the pattern area of the screen and is evenly squeezed onto the interdigital electrode substrate to form a thin film with a specific pattern.
[0090] S3.2, annealing the obtained thin film and the interdigital electrode substrate at 230° C. for 30 minutes in a glove box filled with nitrogen to complete the preparation of the flexible humidity sensor.
[0091] Specifically, the planar flexible PCB circuit board has a size of 1×1.2 cm and a bottom plate thickness of 1 mm.
[0092] Specifically, the effective area of the Cu / Ni electrode of the interdigitated electrode substrate is 8×6 mm, the electrode line width and line gap are both 200 μm, and the thickness is 20 μm.
[0093] Scanning electron microscopy (SEM, Hitachi S-4800) was used to characterize the surface morphology of PEDOT:PSS, Ag and Ag / PEDOT:PSS composites. Figure 2 The morphology of PEDOT:PSS is shown. The material is relatively flat overall, with wrinkles and protrusions on the surface. Figure 3 The SEM image of Ag in the sample shows loosely packed silver nanoparticles. Figure 4 The SEM image of the Ag / PEDOT:PSS composite material is shown. It can be observed that PEDOT:PSS is filled between the loosely packed silver nanoparticles, which is beneficial to improving the conductivity of the composite material. On the one hand, PEDOT:PSS fills the gaps between the loosely packed Ag nanoparticles, fully connects the Ag nanoparticles, reduces the contact resistance between the silver nanoparticles, and thus significantly improves the conductivity of Ag. On the other hand, the Ag in PEDOT:PSS also enhances the conductivity of PEDOT:PSS by providing additional conductive pathways. Figure 5 As shown, the TEM image of PEDOT:PSS shows its film structure. Figure 6 TEM image showing uniformly distributed Ag nanoparticles. Figure 7-Figure 10 From the elemental mapping of the Ag / PEDOT:PSS composite material, it can be seen that Ag, C, O and S elements are evenly distributed in the material, which indicates the successful preparation of the Ag / PEDOT:PSS composite material.
[0094] The Ag, PEDOT:PSS and Ag / PEDOT:PSS samples were characterized by X-ray diffraction (XRD). The X-ray diffractometer used was D8 ADVANCE, and the radiation used was Cu Kα radiation. The results are as follows Fig.11As shown. The diffraction peak of PEDOT:PSS material at 2θ=26° corresponds to the (020) plane of the orthorhombic unit cell. Many diffraction peaks can be seen from the diffraction peak of Ag. The data were taken from the 2θ range of 30 to 80 degrees with a step size of 0.0202 degrees. The data were consistent with the JCPDS standard powder diffraction card (04-0783). In the diffraction pattern, five peaks at 2θ values of 38.18, 44.37, 64.49, 77.46 and 81.57 degrees were identified as Ag, corresponding to the -(111), (200), (220), (311) and (222) planes of Ag. The XRD spectrum of Ag / PEDOT:PSS contains all the diffraction peaks of pure Ag and pure PEDOT:PSS materials, further proving the presence of Ag and PEDOT:PSS. In order to further analyze the elemental composition of the Ag / PEDOT:PSS composite material, the present invention performed XPS characterization on it, such as Figure 11-15 As shown. In the total XPS spectrum of the Ag / PEDOT:PSS composite material, Fig.12 In the figure, the peaks of O, Ag, C and S can be clearly seen, which also proves the successful synthesis of Ag / PEDOT:PSS material. The effect of the addition of Ag on the electronic structure of PEDOT:PSS was analyzed by XPS. Fig.13 The Ag 3d spectrum of the sample accurately determined the double peak characteristics of Ag 3d5 / 2 and Ag 3d3 / 2. The Ag 3d5 / 2 and Ag 3d3 / 2 peaks are located at 368.48 and 374.68 eV, respectively, which indicates that the Ag nanoparticles have a metallic state in PEDOT and PSS. In addition, the O1s spectrum ( Fig.14 ) has a peak at 533 eV, which is related to the C=O bond in PEDOT. The peak near 531 eV is related to the CO bond in PSS. Fig.15 As shown in the figure, the XPS energy level spectrum of C1s has an obvious peak near 284.8eV, which belongs to the CC bond, and a shoulder peak near 286eV, which belongs to the CO bond. At the same time, the C1s spectrum of the sample shows a typical oxygen-containing polymer, with an additional oscillation peak at 298.11eV, corresponding to the OCO bond. Fig.16 As shown, the two XPS peaks of S2p in the binding energy range of 162ev~166ev belong to the S atoms in the PEDOT chain, and the XPS peak of S2p in the binding energy range of 166ev~172ev belongs to the S atoms in the PSS chain.
[0095] The flexible humidity sensor prepared by the present invention is placed in a humidity glass bottle with humidity of 0% to 97% prepared in different saturated salt solutions. After the resistance of the flexible humidity sensor is stable at each humidity, it is placed in 0% humidity to restore its resistance. After the resistance is restored to the initial value, it is placed in the next concentration of humidity for testing.
[0096] Fig.17 The resistance changes of sensors based on pure PEDOT:PSS material and Ag / PEDOT:PSS material at different humidity levels of 11%-97% are shown. The resistance of the sensor increases with the increase in humidity concentration. The resistance of the sensors of PEDOT:PSS and Ag / PEDOT:PSS materials at 0% humidity are approximately 73.2 kΩ and 252.6 kΩ, respectively, which indicates that the doping of Ag reduces the resistance of the sensor. The presence of Ag nanoparticles in PEDOT:PSS increases its highest occupied molecular orbital (HOMO) level and reduces its work function. Reducing the work function can increase the conductivity of PEDOT:PSS. At the same time, the sensor with reduced resistance is more conducive to adapting to the signal acquisition circuit for the integrated design of the humidity monitoring system. In order to better quantify and compare the performance of the sensor, we converted the resistance of the sensor into a response. The responses of the sensors of PEDOT:PSS and Ag / PEDOT:PSS materials at different humidity levels are shown in Figure 2. Fig.18 As shown. It can be seen that the response of the sensor of Ag / PEDOT:PSS material is higher than that of the sensor of PEDOT:PSS material, which indicates that Ag / PEDOT:PSS material has a better humidity sensing effect. The calculation method of response (S) is as follows:
[0097]
[0098] Among them, R g is the resistance of the sensor at a certain humidity concentration. a is the resistance of the sensor in 0% humidity. Fig.19 As shown in the figure, the fitting curves of the sensors of PEDOT:PSS and Ag / PEDOT:PSS materials show that the response of the sensor gradually increases with the increase of humidity concentration. The fitting functions of the resistance value (Y) and relative humidity (X) of the sensors of PEDOT:PSS and Ag / PEDOT:PSS materials are Y=42.4+1.7*X and Y=67.7+1.7*X, respectively, and the regression coefficients R2 are 0.9526 and 0.9571, respectively, indicating that the fitting formula is very accurate.
[0099] Fig. 20 The response changes due to rising humidity (11-97% humidity) and falling humidity (97-11% humidity) are shown. The response curves obtained by the uplink test and the downlink test are basically symmetrical. It is proved that the sensor of Ag / PEDOT:PSS material has excellent adsorption-desorption performance. Based on the above test results, the hysteresis curve is drawn, such as Fig.21 As shown, it can be seen that the hysteresis effect of the sensor made of Ag / PEDOT:PSS material can be ignored.
[0100] Fig. 22 The response / recovery curve of the sensor made of Ag / PEDOT:PSS material at a humidity of 83% is shown. The response / recovery time refers to the time taken for the response value to rise from a stable response value to 90%, and the time taken for the stable response value to drop to 10%. It can be seen from the figure that the response time of the Ag / PEDOT:PSS sensor is 2.3s and the recovery time is 16.2s. Fig.23 As shown in Figure 2, when the humidity level continuously increases from 0% to 97%, the response of the Ag / PEDOT:PSS sensor increases from 0% to 218.35%. The repeatability measurement of the Ag / PEDOT:PSS thin film sensor is shown in Figure 2. Fig.24 As shown in the figure, the resistance values of the Ag / PEDOT:PSS thin film sensor were basically consistent in the three repeated measurements at 10% and 50% humidity. Therefore, the Ag / PEDOT:PSS thin film sensor showed excellent repeatability.
[0101] Finally, the long-term stability of the sensor made of Ag / PEDOT:PSS material was tested. Fig.25 As shown. The response of the sensor was measured every 10 days at humidity of 23%, 43%, and 83%. It can be seen that the response deviation of the sensor of Ag / PEDOT:PSS material at different humidity levels is less than 5% as time increases, indicating that it has excellent long-term stability.
[0102] The high humidity sensing performance of the sensor based on Ag / PEDOT:PSS material originates from the intrinsic synergistic effect of PEDOT:PSS and Ag on water adsorption. H2O molecules can react with the available sites of PSS in PEDOT:PSS. Under high humidity conditions, the sulfonic acid groups in the PSS region are completely deprotonated, resulting in film expansion. Due to this expansion, the distance between adjacent PEDOTs increases. The increased spacing hinders the interchain and hopping conduction of electrons between the PEDOT structures, leading to an increase in resistance. At the same time, the hydroxyl functional groups in PEDOT:PSS can increase hydrogen bonding and interaction with water molecules, thereby achieving a high response of the sensor. At high humidity, hydrogen bonds are combined with water molecules, resulting in a higher level of expansion. Therefore, there will be a larger spacing and higher resistance at high humidity. Ag is a good oxygen adsorption catalyst that can chemically adsorb and dissociate O2 under atmospheric conditions, thereby promoting the interaction between oxygen functional groups and water molecules. The formation of a complex between Ag, PEDOT, and PSS forces PEDOT to undergo conformal changes, resulting in more delocalized charges. Ag nanoparticle clusters may cause PEDOT:PSS molecules to form a morphological structure that is conducive to charge transfer, thereby forming a better conductive channel in Ag / PEDOT:PSS. Therefore, compared with PEDOT:PSS, PEDOT:PSS interacting with Ag nanoparticles provides a larger surface area, which makes the electron transfer between the Ag / PEDOT:PSS film and the surrounding electrolyte faster. At the same time, the enhancement of electron transfer in Ag / PEDOT:PSS materials is also attributed to the charge jump of the metal conductor Ag nanoparticles, which mediate the migration of effective charges in PEDOT:PSS. With the formation of Ag nanoparticles, the structural disorder and π conjugation of PEDOT:PSS increase.
[0103] Embodiment 2
[0104] The flexible humidity sensor provided by the present invention can also be applied to wearable devices.
[0105] The humidity near the mouth and nose of a person changes periodically when he exhales and inhales. By monitoring this humidity change, the breathing frequency of the object under test can be monitored in real time to reflect his work, study, health and other states. Based on the designed Ag / PEDOT:PSS humidity sensor, the present invention designs a wearable respiratory monitoring device. The device integrates high sensitivity and real-time monitoring functions and is suitable for a wide range of health and environmental applications. The data acquisition and wireless transmission system is designed using the STM32F107VCT6 single-chip microcomputer and the Bluetooth wireless transmission module, and the humidity change data caused by breathing can be wirelessly transmitted to mobile phones and computers. At the same time, thanks to the low power consumption characteristics of the Ag / PEDOT:PSS sensor (i.e., the flexible humidity sensor provided by the present invention), the endurance of the device is significantly improved. It has a compact structural size, which is convenient for later wearable integration. By integrating the Ag / PEDOT:PSS humidity sensor into a mask, the collection and wireless transmission of respiratory data to computers and mobile phones can be realized. Fig.26 The response curves of the Ag / PEDOT:PSS humidity sensor during rapid breathing, normal breathing, and rapid breathing are shown. The breathing rates in the three cases are approximately 70 times / minute, 24 times / minute, and 6 times / minute, respectively. When exhaling, the humidity increases, so the response value of the Ag / PEDOT:PSS humidity sensor increases. When inhaling, the humidity decreases, and the response value of the sensor also decreases. At the same time, for people with problems such as asthma, there will be sudden deep breathing and gradual recovery. Therefore, we also tested the response value change curve of the Ag / PEDOT:PSS humidity sensor when breathing deeply first and then gradually becoming shallow, as shown in the figure. Fig. 27 The monitoring device is designed to take into account comfort, stability and data acquisition accuracy, and can meet the needs of healthcare, sports monitoring and other humidity-sensitive application scenarios.
[0106] Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by technicians in this technical field within the essential scope of the present invention should also fall within the protection scope of the present invention.
Claims
1. A programmable robot control system, characterized in that: include: Flexible humidity sensor array, energy storage module, resistance collection device, Bluetooth and robot control terminal; the energy storage module powers the resistance collection device and Bluetooth, the flexible humidity sensor array is connected to the resistance collection device, the resistance collection device uploads the collected data to the robot control system via Bluetooth, the robot control system processes the data and converts the data into corresponding control signals to control the movement of the programmable robot.
2. A programmable robot control system according to claim 1, characterized in that: The resistance acquisition module has multiple channels, and the multiple channels simultaneously acquire the resistance values of multiple flexible humidity sensors on the flexible humidity sensor array.
3. A programmable robot control system according to claim 2, characterized in that: The energy storage module includes: a DC power supply, or a triboelectric nanogenerator TENG, or an electromagnetic generator EMG, or other energy supply equipment.
4. A programmable robot control system according to claim 3, characterized in that: The method for preparing the flexible humidity sensor comprises the following steps: S1, preparation of Ag / PEDOT:PSS material; S2, preparing an interdigitated electrode substrate; S.3, use screen printing to print Ag / PEDOT:PSS material onto the interdigital electrodes to complete the preparation of the flexible humidity sensor.
5. A programmable robot control system according to claim 4, characterized in that: Step S1 specifically includes the following steps: S1.1, prepare 3,4-ethylenedioxythiophene EDOT as a monomer, polystyrene sulfonate PSS as a dopant, and sodium persulfate Na2S2O8 as an oxidant; S1.2, dissolve 2g PSS in 100ml water, and then add 1g Na2S2O8 oxidant to form a uniform solution; S1.3, dissolve 0.5 mM silver nitrate AgNO3 in deionized water to prepare an AgNO3 solution, and add it to the solution obtained in step S2.
6. A programmable robot control system according to claim 5, characterized in that: Step S1 also includes the following steps: S1.4, prepare a reducing agent solution with 10 mM sodium borohydride NaBH4, and slowly drop the NaBH4 solution and 5 g EDOT monomer into the solution under stirring; S1.5, magnetic stirring at 0°C for 24 hours, adding 10 mM citric acid C6H8O7 as a stabilizer and stirring during the reaction to finally obtain a PEDOT / PSS solution doped with Ag nanoparticles; S1.6, after the reaction is completed, the mixture is washed with deionized water to remove residual oxidants and unreacted monomers, and then centrifuged and purified for 10 h in a centrifuge to obtain pure Ag / PEDOT:PSS material.
7. A programmable robot control system according to claim 4, characterized in that: Step S2 specifically includes the following steps: S2.1, select a flat flexible PCB circuit board with polyimide as the substrate; S2.2, uniformly sputtering a layer of Cu / Ni metal film on the surface of the PCB circuit board to form an interdigitated meander-shaped electrode; S2.3, coating a uniform, highly adherent and defect-free photoresist film on the surface of the PCB circuit board by spin coating; S2.4, using a photolithography machine to irradiate the PCB circuit board covered with the mask plate with ultraviolet light, so that the solubility of the photoresist in the illuminated area changes; S2.5, immersing the PCB circuit board covered with the mask plate in a developer to remove the photoresist of the unexposed portion to form a three-dimensional mask pattern; S2.6, using a wet etching technique to remove the Cu / Ni film not protected by the photoresist in the mask pattern, thereby forming a forked-finger metal electrode on the surface of the PCB circuit board; S2.7, removing the remaining photoresist through a stripping process, leaving only the Cu / Ni electrode pattern formed on the surface of the PCB circuit board, thereby forming an interdigitated electrode substrate.
8. A programmable robot control system according to claim 4, characterized in that: Step S3 specifically includes the following steps: S3.1, fix the pre-processed screen printing plate on the interdigital electrode substrate, use a scraper to apply pressure on the interdigital electrode substrate, and move from one end of the screen printing plate to the other end, so that the Ag / PEDOT:PSS material passes through the pattern area of the screen and is evenly squeezed onto the interdigital electrode substrate to form a film with a specific pattern; S3.2, annealing the obtained thin film and the interdigital electrode substrate at 230° C. for 30 minutes in a glove box filled with nitrogen to complete the preparation of the flexible humidity sensor.
9. A programmable robot control system according to claim 7, characterized in that: The size of the flat flexible PCB circuit board is 1×1.2cm and the bottom board thickness is 1mm.
10. A programmable robot control system according to claim 8, characterized in that: The effective area of the Cu / Ni electrode of the interdigitated electrode substrate is 8×6 mm, the electrode line width and line gap are both 200 μm, and the thickness is 20 μm.
Citation Information
Patent Citations
Construction method of molybdenum-disulfide-based gas-sensitive sensing array and application of the same in SF6 gas decomposition component detection
CN110530935A
Non-contact key system
CN110941213A
Preparation method of high-sensitivity non-contact humidity sensor and CNT-SNC dispersion liquid
CN115165972A
Full-fabric-based self-powered multi-element drive sensing system and preparation method and application thereof
CN116105779A
Novel intelligent education robot
CN209132994U